Analysis of the Factors of Success and Failure of Information System Projects in the Public and Private Sectors - Fawad Bikzad; Farid Ullah Qayoumi (Journal of International Accounting, Taxation and Information Systems, 2026)
Information system (IS) projects represent substantial investments for public and private organizations, yet many fail to achieve their intended objectives. Despite advances in project management practices and information technologies, project failure remains a persistent challenge. Global IT investment reached approximately USD 3.11 trillion in 2022, while Standish Group CHAOS reports indicate that only about one-third of projects are completed on time, within budget, and with the required functionality. This systematic literature review synthesizes evidence from 67 studies published between 1990 and 2024 to examine how organizational, managerial, and technical factors influence IS project success and failure. Guided by a critical realist perspective and thematic synthesis, the review identifies critical success factors, explores relationships among failure factors, and compares priorities across public and private sectors. The findings reveal that people-related factors including committed project teams, active user involvement, clearly defined requirements, effective leadership, and executive support have the strongest influence on project success. While many success factors are common to both sectors, public organizations place greater emphasis on stakeholder engagement, governance, procurement compliance, and change management, whereas private organizations prioritize cost efficiency, rapid delivery, innovation, and technical performance. User participation, communication, and training consistently strengthen other success factors. The review extends the DeLone and McLean IS Success Model by incorporating project-level determinants and supports a contingency perspective, offering practical guidance for project managers, IT executives, and policymakers to improve IS project outcomes.